Perbedaan Glasgow Coma Scale dan Rapid Emergency Medicine Score dalam Memprediksi Outcome Pasien Trauma Kepala di Instalasi Gawat Darurat - Didik Mulyono (Politeknik Kesehatan Tanjung Karang, 2020)
Initial assessment of patients with head trauma is an influence on the management of patients with head trauma. GCS was developed to describe the level of consciousness in patients with head trauma. Whereas REMS is a scoring system that has been used widely in various countries to predict the mortality of patients coming to the emergency room. The purpose of this study was to determine the differences in the effectiveness of REMS and GCS scoring on the outcome of head trauma patients in the Emergency Departement. This study uses an analytic observational design with a retrospective cohort approach. The sample consisted of 181 patients where the sampling was carried out using a purposive sampling technique in which the researchers selected samples according to the inclusion and exclusion criteria of the existing population. Bivariate analysis conducted in this study used the Somers'd test and the Spearman test. The Area Under Receiver Operating Characteristics (AUROC) is used to assess the ability of REMS and GCS scoring to distinguish good outcomes and bad outcomes. The results of this study indicate that REMS and GCS scoring has a p-value<0,05 which means there is a significant relationship with the outcome of head trauma patients. From the results of the AUROC analysis, the AUC value was 0.753 for REMS, and the AUC was 0.769 for GCS. The ability of REMS and GCS to predict the outcome of head trauma patients shows good performance. So that both can be considered used as an early detection system or Early Warning Score System (EWSS) in head trauma patients in the Emergency Departement.